Trematode (Digenea) infestation on freshwater snails (Mollusca: Gastropoda) collected off rivers of Crocker Range Park, Sabah - Jasrul Dulipat (2019)
Freshwater snail is the first intermediate host for trematode parasite that can cause snail-borne diseases in human as well as animals. This study is the first kind that deals with the parasitology of freshwater snail population in rivers around the Crocker Range Park, Sabah. The objectives of this study are to determine the parasite prevalence of freshwater snail species in rivers in this study, to compare parasite prevalence between disturbed and undisturbed rivers, to establish a checklist of trematode parasite infesting freshwater snail and finally to compare freshwater snail diversity between disturbed and undisturbed rivers in this study. This study was conducted in 14 rivers consist of seven disturbed and seven undisturbed rivers and sampling was conducted for seven monnths from July 2017 to January 2018. Snails were collected from each river and observed for parasite infestation. Parasite prevalence and snail diversity were then compared between disturbed and undisturbed rivers by using Mann-Whitney U test and Sample based rarefaction curve respectively. A total of five morpho-types of trematode parasite, which consist of 11 different species were released from 1709 individuals of freshwater snail belong to 10 species and nine families collected from 14 rivers in this study. The overall parasite prevalence of the freshwater snail species was 4.45%. Unidentified snail species under the family of Hydrobidae showed the highest parasite prevalence followed by Paludomus sp. (Paludomidae) and Clea sp. (Pachychilidae), whereas three species of snail which are Slnotala guangdungensis (Viviparidae), Pomacea sp. (Ampillaridae) and Physa acuta (Physidae) recorded with zero prevalence. The comparison between undisturbed and disturbed rivers for parasite prevalence showed that there was a significant difference (p<0.05) where undisturbed rivers (11.30%) are more prevalent compared to disturbed river (3.66%). All parasites reported in this study considered as new record to Sabah. Freshwater snail species richness and diversity comparison between the two types of rivers in this study showed significant difference where disturbed rivers contain higher diversity and more specious (0=8, 1=3.822, 2=2.881) compared to undisturbed rivers (0=3, 1=2.55, 2=2.44). This study has provided useful information regarding freshwater snail parasitology in Malaysia.